Distinct Functions of Bombyx mori Peptidoglycan Recognition Protein 2 in Immune Responses to Bacteria and Viruses - Jiang, Liang; Liu, Weiqiang; Guo, Huizhen; Dang, Yinghui; Cheng, Tingcai; Yang, Wanying; Sun, Qiang; Wang, Bingbing; Wang, Yumei; Xie, Enyu; Xia, Qingyou (Frontiers in Immunology, 2019)
Peptidoglycan recognition protein (PGRP) is an important pattern recognition receptor in innate immunity that is vital for bacterial recognition and defense in insects. Few studies report the role of PGRP in viral infection. Here we cloned two forms of PGRP from the model lepidopteran Bombyx mori: BmPGRP2-1 is a transmembrane protein, whereas BmPGRP2-2 is an intracellular protein. BmPGRP2-1 bound to DAP-type PGN to activate the canonical Imd pathway. BmPGRP2-2 knockdown reduced B. mori nucleopolyhedrovirus (BmNPV) multiplication and mortality in cell lines and in silkworm larvae, while its overexpression increased viral replication. Transcriptome and qPCR results confirmed that BmPGRP2 negatively regulated PTEN. BmPGRP2-2 expression was induced by BmNPV, and the protein suppressed PTEN-PI3K/Akt signaling to inhibit cell apoptosis, suggesting that BmNPV modulates BmPGRP2-2-PTEN-PI3K/Akt signaling to promote viral infection. These results demonstrate that the two forms of BmPGRP2 have different functions in host responses to bacteria and viruses.